2021
DOI: 10.1097/cco.0000000000000781
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and quality of life in patients with early-stage breast cancer receiving adjuvant endocrine therapy

Abstract: Purpose of reviewA comprehensive approach to survivorship care for women with early-stage, hormone-receptor positive breast cancer should systematically include the proactive assessment and adequate management of endocrine therapy-associated symptoms, in order to assure optimal balance between preserving quality of life (QOL) and maximizing treatment adherence. We reviewed the recent literature focused on lifestyle factors, including physical activity, diet and nutrition, weight management, smoke, and alcohol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…A significant correlation was observed between a healthy lifestyle and quality of life scores in breast cancer survivors. In similar studies, having a healthy lifestyle, including adequate exercise, proper consumption of fruits and vegetables, weight loss, and satisfactory sleep, effectively improved the quality of life concerning the health of breast cancer survivors [25][26][27][28]. Improving quality of life can also be associated with favorable prognosis and lower mortality in breast cancer survivors [28].…”
Section: Discussionmentioning
confidence: 88%
“…A significant correlation was observed between a healthy lifestyle and quality of life scores in breast cancer survivors. In similar studies, having a healthy lifestyle, including adequate exercise, proper consumption of fruits and vegetables, weight loss, and satisfactory sleep, effectively improved the quality of life concerning the health of breast cancer survivors [25][26][27][28]. Improving quality of life can also be associated with favorable prognosis and lower mortality in breast cancer survivors [28].…”
Section: Discussionmentioning
confidence: 88%
“… 34 Previous studies have used feasibility studies prior to conducting a study in a larger setting. 9 35 The intervention was developed to encourage patients to be more actively involved in their care and well-being as partners with their contact nurse. 10 It has been stated that an intervention could be considered complex due to the behaviours required by those delivering the intervention, 36 that is, a contact nurse.…”
Section: Introductionmentioning
confidence: 99%
“…Other challenges that have been identified include older age,7 medicine costs or a general dislike of taking a regular medicine 8. As ET is a long-lasting treatment, women may request support in managing challenges 9. To manage challenges with ET, a partnership with healthcare professionals could be appropriate, as a previous study10 identified that women with ET want to be able to manage their treatment but need guidance to do so.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Despite the side effects such as night sweats, hot flushes, joint and muscle pain, vaginal dryness, and others being relatively common occurring in up to 70% of patients, personal interpretation of these symptoms and their impact on the patient's quality of life (QoL) widely differ. 7,8 In an advanced BC stage, where the endocrine therapy effect on the disease is more apparent by decreasing metastasis and tumor mass, side effects are better tolerated and therefore lead to only a marginal non-acceptance. 9 On the other hand, in early BC, the benefit of AET cannot be experienced immediately, whereas the side effects may have a direct impact on the QoL.…”
Section: Introductionmentioning
confidence: 99%